Combination of cortical-subcortical infarction with lobar microbleeds as a specific MRI pattern in patients with infective endocarditis - Dmitry A. Demin; Aleksey A. Kulesh; Ekaterina V. Nikolaeva; Elena I. Shaposhnikova; Marina V. Lezhikova; Pavel A. Astanin (ZAO "Consilium Medicum", 2023)
Background. Ischemic stroke (IS) and cerebral microbleeds (CMB) are the most common types of neurological complications of infective endocarditis (IE), while their combination is poorly understood. Aim. To evaluate the pattern of combination of cortical-subcortical infarction with lobar CMB or subarachnoid hemorrhage (SAH) in patients with left-sided IE. Materials and methods. A retrospective case-control study was conducted, including patients with IE who received cardiac surgery at the Federal Center for Cardiovascular Surgery. Inclusion criteria: age of patients 18 years; definite or possible (Duke criteria) IE of the left heart (aortic and/or mitral valves). The control group included patients without IE, with non-lacunar (likely embolic) IS. In both groups, the pattern of combination of cortical-subcortical infarction with lobar CMB or SAH was assessed. Differences between groups of patients were assessed using the 2 test, Fisher's exact test and the MannWhitney test. Additionally, odds ratios for binary features were calculated. To assess the information content of the studied pattern, classical classification quality metrics were calculated: accuracy, sensitivity, and specificity. Results. In patients with IS, infarcts corresponded to the main characteristics of cardioembolism: involvement of multiple cerebral arterial territories (84%), multiple infarcts (88%), cortical-subcortical localization (100%), and a high incidence of hemorrhagic transformation (44%). CMB was detected in 64% of cases (in 93.8%, CMB localization was lobar), SAH in 28% of patients (with CMB in 6 out of 7 cases). The pattern of combination of cortical-subcortical infarction with lobar CMB or SAH was observed in 64% in the IE group (in the control group in 12%). Odds ratio for the presence of IE was 13.0 (95% confidence interval 3.0455.9; p0.001). The accuracy of the sign was 76%, specificity 71%, sensitivity 84%. Conclusion. The combination of cortical-subcortical infarcts with lobar CMB or SAH may be a sign characteristic of IE-associated stroke.